Jesus the purifier John's gospel and the fourth quest for the historical jesus - Blomberg, Craig L. 1955- (Grand Rapids Baker Academic, 2023)
Intro -- Half Title Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Abbreviations -- Introduction -- 1. The Original Quest for the Historical Jesus -- 2. No Quest and New Quest? -- 3. Launching the Third Quest with a Jewish Jesus -- 4. The Jesus Seminar and Its Kin: A Step Back in Time -- 5. Has the Third Quest Played Itself Out? -- 6. Foreshadowing the Fourth Quest: Rehabilitating the Gospel of John -- 7. Purification, Baptism, and Transformation in John 1-4 -- 8. Purification Starting to Change in John 5-11 -- 9. Ritual Purity Fades Away in John 12-21 -- 10. Purity and the Historical Jesus of the Synoptics -- Conclusion -- Index of Authors -- Index of Scripture and Other Ancient Writings -- Cover Flaps -- Back Cover.
A leading New Testament scholar explains that a fourth quest for the historical Jesus is underway, one that highlights the contribution of the Gospel of John and recognizes Jesus as Purifier.
Description based on publisher supplied metadata and other sources
Keywords: Jesus Christ -- Historicity; Bible -- Criticism, interpretation, etc; Electronic books